Synthesis of Cinnamic Acid from Benzoin Extract Using Sulfuric Acid as a Catalyst - Junaldo Andreas Pardede; Marham Sitorus (Universitas Negeri Medan, 2025)
This study explores the synthesis of cinnamic acid from benzoin extract using sulfuric acid as a catalyst. Benzoin resin was extracted to obtain cinnamyl cinnamate, which was then hydrolyzed under acidic conditions to yield cinnamic acid. The synthesized compound was characterized using Fourier- transform infrared (FTIR) spectroscopy and gas chromatography-mass spectrometry (GC-MS). The FTIR spectra confirmed the presence of characteristic functional groups of cinnamic acid, while GC- MS analysis verified its purity and molecular structure. The optimized reaction conditions provided a significant yield, indicating the efficiency of this method in producing cinnamic acid from a natural source.